Oil Production and Economic Growth in Angola - Mohammed, Mikidadu (International Journal of Energy Economics and Policy, 2018)
This study examines the relationship between oil production and economic growth in Angola for the period of 1985-2015. Relying upon the estimation of autoregressive distributed lag (ARDL) model, the study finds that oil production and economic growth are cointegrated. Furthermore, there is positive unidirectional causality from oil production to economic growth in the long run which supports policies about investing in energy infrastructure. However, the absence of reverse causality from economic growth to oil production underscores Angola’s heavy reliance on external demand for its oil to drive economic growth. Thus, policymakers should also consider diversifying the economy to other growing sectors to mitigate the impact of adverse global economic shocks associated with sharp decline in global oil demand. Keywords: oil production, economic growth, Granger causality JEL Classifications: Q40; Q43; C01